Changes in Agricultural Markets in Poland following its Accession to the European Union = Zmiany na rynkach rolnych w Polsce po akcesji do Unii Europejskiej - Czyżewski, Andrzej; Czakowski, Dariusz (Zielona Góra: Faculty of Economics and Management Press)
This article attempts to determine the most significant tendencies and changes observed in Poland?s core markets of agricultural products, which occurred during the period preceding Poland`s accession to the European Union (1994-2003) and after the accession (2004-2013). The key markets of agricultural products include markets with the largest value of commodity production during the analysed period, such as cereals, potatoes, sugar beet, rapeseed, fruit, vegetables, pork, beef and poultry, cows` milks and eggs.
Keywords: rynki rolne; integracja europejska; agricultural markets; European integration